Outer membrane vesicles in gram-negative bacteria and its correlation with pathogenesis - Abolhasani, Fatemeh Sadat; Vaghefinanekaran, Nasim; Yarahmadi, Aref; Akrami, Sousan; Mirmahdavi, Solmaz; Yousefi, Mohammad Hasan; Afkhami, Hamed; Shafiei, Morvarid (Frontiers in Immunology, 2025)
There is a widespread distribution of gram-negative bacteria worldwide, which are responsible for the deaths of numerous patients each year. The illnesses they cause can be localized and systemic, and these bacteria possess several key virulence factors that contribute to their pathogenicity. In recent years, several distinct mechanisms of pathogenesis have evolved that remain largely unknown to scientists and medical experts. Among these, outer membrane vesicles (OMVs) are undoubtedly one of the most significant factors influencing virulence. OMVs contain various bacterial compounds and can have diverse effects on host organisms and the immune system, potentially exacerbating disease and inflammation while evading immune responses. This review comprehensively examines the role of OMVs in bacterial pathogenesis, their interaction with host cells, and their potential biomedical applications. Understanding the molecular mechanisms governing OMV biogenesis and function could pave the way for novel antimicrobial strategies and therapeutic interventions.